Quantitative iron–neuromelanin MRI associates with motor severity in Parkinson's disease and matches radiological disease classification - Hartono, Septian; Chen, Robert Chun; Welton, Thomas; Tan, An Sen; Lee, Weiling; Teh, Peik Yen; Chen, Celeste; Hou, Wenlu; Tham, Wei Ping; Lim, Ee Wei; Prakash, Kumar M.; Shih, Yao-Chia; et al. (Frontiers in Aging Neuroscience, 2023)
Neuromelanin-and iron-sensitive MRI studies in Parkinson's disease (PD) are limited by small sample sizes and lacked detailed clinical correlation. In a large case-control PD cohort, we evaluated the diagnostic accuracy of quantitative iron-neuromelanin MRI parameters from the substantia nigra (SN), their radiological utility, and clinical association.PD patients and age-matched controls were prospectively recruited for motor assessment and midbrain neuromelanin-and iron-sensitive [quantitative susceptibility mapping (QSM) and susceptibility map-weighted imaging (SMWI)] MRI. Quantitative neuromelanin-iron parameters from the SN were assessed for their discriminatory performance in PD classification using ROC analysis, compared against those of qualitative visual classification by radiological readers of differential experience, and used to predict motor severity.191 subjects (80 PD, mean age 65.0 years; 111 controls, 65.6) were included. SN masks showed (a) higher mean susceptibility (p<0.0001) and smaller sizes after thresholding for low susceptibility (p<0.0001) on QSM, and (b) lower contrast range (p<0.0001) and smaller sizes after thresholding for high signal voxels (p<0.0001) on neuromelanin-sensitive MRI than in patients than controls. Quantitative iron and neuromelanin parametersMasks sizes showed moderate negative correlation with motor dysfunction (87.5%: 0.4<  r  <0.6r -0.445 and -0.417, p<0.0001) respectively. A composite quantitative neuromelanin-iron marker differentiated the groups with 4 excellent performance (AUC 0.94), matching the diagnostic accuracy of the best performing reader (accuracy 97%) using SMWI.Quantitative neuromelanin-iron MRI are associated with PD motor severity and matched bestperforming radiological PD classification using SMwI, with potential to improve diagnostic confidence in the clinics, and track disease progression and response to neuroprotective therapies.